NILAI RELIGIUSITAS NASKAH KUNO SERAT SULUK BABARANING NGELMI MAKRIFAT - Tsurayya, Nabhana Aida (ESTETIKA: JURNAL PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2023)
Literary and cultural works are open systems that are closely related to cultural integrals. Serat Suluk Babaring Ngelmi Makrifat or commonly abbreviated as SSBM can be classified as works of religious literature. This study aims to present a description, manuscript transliteration and translation of the ancient text of Serat Suluk Babaring Ngelmi Makrifat. This type of research uses a qualitative description. The source of the data in this study was the manuscript Serat Suluk Babaring ngelmi Makrifat by NN (No Name) with codex number A.70. The data of this research is the text of Serat Suluk Babaring ngelmi Makrifat in the form of words, sentences, and the transliteration and translation results of descriptions of religious values. This research uses the term human instrument based on the ability of researchers to analyze precisely through the data that has been found. Therefore, researchers equip themselves with research approaches, content analysis, identify and clarify data that contains religious values. Data analysis technique used content analysis technique (content analysis). Presentation of the results of the analysis using informal methods. The results of this study indicate that there are religious values found in the SSBM text, namely piety, forgiveness, monotheism, and physical and spiritual balance.